EFEKTIVITAS METODE PEMBELAJARAN BERBASIS LABORATORIUM UNTUK MENINGKATKAN PEMAHAMAN MATERI GERAK PELURU DI AAU - Resia, Made (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2022)
In the process of learning physics, various methods have been carried out such as lectures and discussions as well as questions and answers, but the results have not been as expected. In fact there are still cadets who find it difficult to learn physics because there are too many formula. Plus the lack of interest from cadets to learn physics so that the understanding of physics material is decreasing. In overcoming this problem the author will try to use laboratory-based learning methods. The Air Force Akademy (AAU) as the sentral implementing agency at Mabesau level located directly under Kasau, who has the main task of organizing the first aducation of Indonesian Air Force voluntary officers with an akademic level characterized by Sapta Marga warriors who have akademic abilities the basic potential of the air matrix, as well as physical opportunities to support tasks in their service as a defence force. From the main tasks carried AAU, the Cadets should get a good learning model, one off them Laboratory-Based learning. This is one of the efforts to improve the quality of fhysics learning especially on bullet motion material to make it more interesting and fun. With interesting and fun learning a more oftimal interest and understanding will be obtained. The purpose of this study was to determine yhe effect of using the laboratory in the form of demonstrations and experiments on interest and understanding of bullet motion material.